2016
DOI: 10.1016/j.soildyn.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of capacity design of columns in steel moment resisting frames with viscous dampers

Abstract: Previous research showed that steel moment-resisting frames (MRFs) with viscous dampers may experience column plastic hinges under strong earthquakes and highlighted the need to further assess the efficiency of capacity design rules. To partially address this need, three alternatives of a prototype building having five, 10 and 20 stories are designed according to Eurocode 8 using either steel MRFs or steel MRFs with dampers. Incremental dynamic analysis (IDA) is conducted for all MRFs and their collapse resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The same work provided evidence that the formation of column plastic hinges in steel MRFs with viscous dampers does not necessarily lead to worst collapse resistance. A recent work extended the study of Seo et al (2014) to the case of 10-story and 20-story buildings and showed a clear trend of tall steel MRFs with viscous dampers to develop plastic mechanisms that involve column plastic hinges (Karavasilis 2016). The latter work also revealed that column plastic hinges are not particularly detrimental in terms of the collapse resistance and reparability of steel MRFs with viscous dampers.…”
Section: Introductionmentioning
confidence: 61%
“…The same work provided evidence that the formation of column plastic hinges in steel MRFs with viscous dampers does not necessarily lead to worst collapse resistance. A recent work extended the study of Seo et al (2014) to the case of 10-story and 20-story buildings and showed a clear trend of tall steel MRFs with viscous dampers to develop plastic mechanisms that involve column plastic hinges (Karavasilis 2016). The latter work also revealed that column plastic hinges are not particularly detrimental in terms of the collapse resistance and reparability of steel MRFs with viscous dampers.…”
Section: Introductionmentioning
confidence: 61%
“…10 that the addition of dampers slightly increased the base shear compared to the bare frame, in the order to 10-15% for the considered distributions. It should be noted that the presence of NVDs may also increase the axial force in the columns, which may require supplemental strengthening of foundations and columns in view of capacity design principles (Karavasilis 2016). Generally, the most critical columns are those located near the supporting braces where the dampers are installed.…”
Section: Seismic Performance Assessmentmentioning
confidence: 99%
“…The behavior of these devices strictly depends on the fluid velocity. Viscous fluid dampers are very versatile and can be designed to allow unconstrained slow thermal motions as well as to provide controlled damping of a structure to protect from wind or earthquakes (Del Gobbo et Al., 2018; Karavasilis et Al., 2016;; De Domenico and Ricciardi 2019). They are typically employed in flexible structures subjected to large and rapid movements like bridges and tall buildings.…”
Section: Introductionmentioning
confidence: 99%